Mudharabah Sebagai Produk Pembiayaan Perbankan Syariah Perspektif Abdullah Saeed - Qomar, Moh. Nurul (MALIA: Journal of Islamic Banking and Finance, 2018)
The aim of this research is to explore Abdullah Saeed's views on the practice of mudharabah contracts in Islamic banking. This research uses library research method and use a research to life history approach. Saeed's findings in the practice of mudharabah contracts in Islamic banking have constraints starting from capital, management, the validity period of contracts, guarantees, profit and loss principles that are different from the concept of mudharabah that develops in the science of fiqh. Abdullah Saeed concluded that the mudharabah contract in Islamic banks was different from the mudharabah contract that developed in the science of fiqh.